Crustal structure beneath the Jiaodong Peninsula, North China, revealed with a 3D inversion model of magnetotelluric data. (3rd August 2018) - Zhang, Kun; Lü, Qingtian; Yan, Jiayong; Hu, Hao; Fu, GuangMing; Shao, Lusen
Abstract: The Jiaodong Peninsula in North China is an important Chinese gold mining region, and deposits are mainly controlled by the northeast trending Sanshandao, Jiaojia, and Zhaoyuan–Pingdu faults. Most previous study results proposed the relationships of the known deposits, controlling faults and regional tectonics. One important tectonic belt, the Sulu Orogen, is thought to be related with mineralization and controlling faults. But debates remain concerning the orogeny boundary and tectonic process. We arranged 32 magnetotelluric stations in one line across the central and southern Jiaodong area to analyze the deep electrical structure of this orogeny. After the data collection (using Phoenix instruments) and pre-processing (Phoenix software), we carried out impedance analysis, data selection, static shift correction and three-dimensional inversion using our software. The results consequently proposed that the distribution of upwelling hydrous basaltic magma acts as conductor in the lower crust. We also proposed the boundary of the North China Block and the Sulu Orogenic Belt by the difference of electrical structure, and suggested a possible collision–coupling process. After the formation of the Jiaobei uplift and Sulu Belt in the subduction process, the tectonic regime was transformed from compression to extension indicated by the conductors. The clockwise rotation of the Yangtze Block might be carried out under the extension setting with the southern Dabie Belt acting as the stress fulcrum.